(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract. Decision on state support for the further development of mathematics education and sciences, as well as measures to radically improve the activities of the V.I.Romanovsky Institute of Mathematics of the Academy of Sciences of the Republic of Uzbekistan, and on May 7, 2020, "In the field of mathematics" "On measures to increase the quality of education and develop scientific research" was adopted. Of course, these are the stages of development of educational areas, aimed at increasing the quality and efficiency of the educational process.